2022
DOI: 10.1186/s12909-022-03675-2
|View full text |Cite
|
Sign up to set email alerts
|

Medical and pharmacy students’ perspectives of remote synchronous interprofessional education sessions

Abstract: Background Interprofessional education (IPE) at university level is an essential component of undergraduate healthcare curricula, as well as being a requirement of many associated regulatory bodies. In this study, the perception of pharmacy and medical students’ of remote IPE was evaluated. Methods A series of IPE sessions took place via Zoom and students’ feedback was collected after each session. Both qualitative and quantitative data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“… Cognitive presence Triggering events Guidance prompts or questions [ 40 , 59 ] Micromovies/videos [ 51 , 69 ] Exploration and integration Joint responsibility, joint discussion and mutual revision [ 47 , 54 ] Assignments that promote sharing experiences and exploring one’s own and others’ opinions or perspectives could be seen as potential facilitators of exploration [ 68 ]. Dividing tasks between group members working individually [ 47 , 54 ] Teaching presence Design and organization Smaller groups [ 36 , 62 , 64 ] 3–4 students per group [ 38 , 47 , 59 ] Choosing their team [ 63 ] Being in the same group over time [ 47 , 48 ] Groups with diversity in health professional fields [ 46 , 70 ] Problem-, or case-based assignments [ 47 , 48 ] Access to relevant learning resources before and throughout group work was found to be beneficial [ 32 , 51 ] Activities or requirements that supported group organization and regulation [ 56 , 58 ] Peer-to-peer feedback [ 33 ] or expectations of peer assessment [ 37 ], Lack of time management for groups could be a potential barrier [ 45 ]. Facilitating discourse Discussion prompts seemed to enhance achievement [ 40 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Cognitive presence Triggering events Guidance prompts or questions [ 40 , 59 ] Micromovies/videos [ 51 , 69 ] Exploration and integration Joint responsibility, joint discussion and mutual revision [ 47 , 54 ] Assignments that promote sharing experiences and exploring one’s own and others’ opinions or perspectives could be seen as potential facilitators of exploration [ 68 ]. Dividing tasks between group members working individually [ 47 , 54 ] Teaching presence Design and organization Smaller groups [ 36 , 62 , 64 ] 3–4 students per group [ 38 , 47 , 59 ] Choosing their team [ 63 ] Being in the same group over time [ 47 , 48 ] Groups with diversity in health professional fields [ 46 , 70 ] Problem-, or case-based assignments [ 47 , 48 ] Access to relevant learning resources before and throughout group work was found to be beneficial [ 32 , 51 ] Activities or requirements that supported group organization and regulation [ 56 , 58 ] Peer-to-peer feedback [ 33 ] or expectations of peer assessment [ 37 ], Lack of time management for groups could be a potential barrier [ 45 ]. Facilitating discourse Discussion prompts seemed to enhance achievement [ 40 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“… Facilitating discourse Discussion prompts seemed to enhance achievement [ 40 , 59 ]. Unclear instructions and explanations were suggested as a potential barrier in several studies [ 32 , 44 , 46 ]. Outside CoI Agreeing on digital tools or social media between students to use for communication and collaboration [ 61 ] Using well-known digital tools or social media [ 39 , 49 , 50 , 60 , 61 ] Technical challenges [ 50 , 57 , 60 ] Internet connection [ 34 , 49 , 59 , 63 ] Lag time [ 55 ] Insufficient instruction or competence in using technology as a potential barrier [ 60 , 65 , 68 ] Scheduling group meetings as a barrier [ 34 , 43 , 44 , 50 , 61 , 62 , 64 , 68 ] Find time to work individually on group assignments [ 35 ] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Medical and pharmacy faculty developed a series of distant synchronous IPE sessions focused on safe prescribing that resulted in students' increased understanding of each other's professional roles and improved the skills required for prescribing. 12 Research supports that educators should be aware of the importance of teaching presence and faceto-face interaction when planning distant educational experiences. 10 A recent review reported limitations of distance education included a lack of personal contact and face-to-face interaction.…”
mentioning
confidence: 96%
“…A recent review found that simulation-based education improved team communication during the simulation and in the clinical environment post-simulation 11. Medical and pharmacy faculty developed a series of distant synchronous IPE sessions focused on safe prescribing that resulted in students' increased understanding of each other's professional roles and improved the skills required for prescribing 12…”
mentioning
confidence: 99%